Micropulse cyclophotocoagulation in the treatment of various types of glaucoma. Part 2: MPCPC at different stages of glaucoma, in combined ophthalmopathology and in congenital glaucoma - O. V. Ermakova; E. A. Ragozina (Российский офтальмологический журнал)
Micropulse cyclophotocoagulation (MPCPC) is a relatively new method of laser treatment of glaucoma, which has actively entered clinical practice due to its effectiveness, relative safety, technical simplicity of implementation and speed of training. The first part of the review presents the history, mechanisms of action and protocol for performing MPCPC [ROJ. 2024; 17 (4): 111–115]. The second part of the review is devoted to the place of MPCPC in the stepwise paradigm of glaucoma treatment, including in patients with high visual acuity. An analysis of existing publications on the possibility of using MPCPC in patients with combined pathology and in children is also presented.